Daily and season-long fantasy sports participation and gambling-related problems among a sample of college students at three universities. Issue 3 (2nd September 2018) - Martin, Ryan J.; Nelson, Sarah E.; Gallucci, Andrew R.; Lee, Joseph G. L.
ABSTRACT: Traditionally, fantasy sports have been played in season-long leagues, but recently daily fantasy sports (DFS) have emerged, allowing participants to play fantasy contests over shorter periods of time. Although participating in fantasy sports contests with entry fees or deposits could be considered a form of gambling, very few studies have examined associations between fantasy sport participation and gambling-related problems. Using a 2016 sample of college students (N = 941) at three institutions, this study examined associations between fantasy sports participation (season-long and DFS) and (1) gambling, (2) gambling frequency, and (3) endorsing DSM-5 gambling disorder (GD) criteria. The study found that engagement with fantasy sports and paying to play increased the likelihood of gambling and more frequent gambling. Respondents who paid an entry fee/deposit to play fantasy sports gambled more frequently than those who did not, and respondents who participated in DFS endorsed more DSM-5 GD criteria than those who did not. Because of the association found between DFS play and gambling-related problems in some participants, the study suggests that mental health professionals who treat clients with gambling problems be cognizant of DFS and that some clients might be experiencing problems with DFS.